2020
DOI: 10.1038/s41598-020-57929-4
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic characterization of families with complex intellectual disability identified pathogenic genetic variations in known and novel disease genes

Abstract: Intellectual disability (ID), which presents itself during childhood, belongs to a group of neurodevelopmental disorders (NDDs) that are clinically widely heterogeneous and highly heritable, often being caused by single gene defects. Indeed, NDDs can be attributed to mutations at over 1000 loci, and all type of mutations, ranging from single nucleotide variations (SNVs) to large, complex copy number variations (CNVs), have been reported in patients with ID and other related NDDs. In this study, we recruited se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Since Garcia CC et al rstly connected SYN1 mutation with neurodevelopmental disorder in 2004, 16 causative variants including ten missense mutations, ve nonsense mutations, and one splicing site mutation in the gene have been identi ed (containing this study) (Fig. 2) [1,2,[7][8][9][10][11][12][13][14][15][16]. These variants are clustered in B linker domain (A51G, S79W), actin-binding and synaptic-vesicle binding C-domain (W126X, W126R, c.527+1G>A, S212I, G240R, V266M, W356X, T359K, R420G) and proline-rich D-domain (R422X, Q482X, A550T, Q555X, T567A) of the encoded protein as indicated (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since Garcia CC et al rstly connected SYN1 mutation with neurodevelopmental disorder in 2004, 16 causative variants including ten missense mutations, ve nonsense mutations, and one splicing site mutation in the gene have been identi ed (containing this study) (Fig. 2) [1,2,[7][8][9][10][11][12][13][14][15][16]. These variants are clustered in B linker domain (A51G, S79W), actin-binding and synaptic-vesicle binding C-domain (W126X, W126R, c.527+1G>A, S212I, G240R, V266M, W356X, T359K, R420G) and proline-rich D-domain (R422X, Q482X, A550T, Q555X, T567A) of the encoded protein as indicated (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To better understand the clinical characteristics of SYN1-related disorder, we conducted a literature review of all reported pedigrees from the Pubmed and Embase on English articles. Clinical information of 7 pedigrees with the disorder from 7 studies was collected in the report (Table 1) [2,[9][10][11][12][13][14], and other cases were excluded for lack of detail descriptions [1,7,8,15,16]. Overall, we noticed that females are less susceptible than males due to X-chromosome random inactivation (XCI), however, few female carriers presented with mild intellectual disability and febrile seizures [8,14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Defects in this gene result in MPS III B (MIM# 252920) [35] which is characterized by intralysosomal accumulation and urinary excretion of heparan sulfate. The p.Asp312Asn NAGLU pathogenic variant has already been reported in two independent studies [18,36]. It was first identified in a French patient [18] in heterozygosity with yet another MPS IIIB-causing variant p.Arg565Gln [37].…”
Section: Mucopolysaccharidoses: Pasp312asn (Naglu Gene)mentioning
confidence: 99%